2018
DOI: 10.1186/s13570-018-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of woody invasive alien plant species on rural livelihood: Generalized propensity score evidence from Prosopis spp. invasion in Afar Region in Ethiopia

Abstract: This study applied a generalized propensity score method to evaluate the impact of Prosopis invasion on Afar pastoralist and agro-pastoralist households' annual per capita consumption expenditure, as a proxy of rural livelihoods. The analysis was based on cross-sectional survey data collected in mid-2016 from 250 households in the Afar National Regional State in Ethiopia. The method was applied to match households with similar covariates with different Prosopis invasion levels. The method was effective in teas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…According to the perception of many pastoralists, livestock are everything for them (sources of food, income, security, social status, cultural value, insurance, etc.) and therefore, there are willing to pay any sacrifices to get forage and water for these animals ( Bekele et al., 2018 ). This issue goes beyond biodiversity and economic reasons and has peace and security elements calling for integrated and coordinated actions at Federal and Regional levels to eradicating or minimizing the negative impacts of P. juliflora on pastoral production system ( Rogers et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the perception of many pastoralists, livestock are everything for them (sources of food, income, security, social status, cultural value, insurance, etc.) and therefore, there are willing to pay any sacrifices to get forage and water for these animals ( Bekele et al., 2018 ). This issue goes beyond biodiversity and economic reasons and has peace and security elements calling for integrated and coordinated actions at Federal and Regional levels to eradicating or minimizing the negative impacts of P. juliflora on pastoral production system ( Rogers et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Now, the species is listed among the world's ten worst invasive weeds ( Shrestha et al., 2018 ) and emerged as a significant threat to Africa's ecological landscapes ( Wakie et al., 2014 ). Nationally, the species is one of the worst invasive species, threatening the environment in arid and semi-arid ecosystem of Africa, and affect the livelihood of pastoral and agro-pastoral society ( Bekele et al., 2018 ; Mbaabu et al., 2019 ; Shackleton et al., 2015 ; Zeray et al., 2017 ). Recent studies showed that rate of P. juliflora invasion is increasing significantly, suppressing native plant species ( Ayanu et al., 2014 ; Haregeweyn et al., 2013 ; Shiferaw et al., 2019c , Shiferaw et al., 2019d ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical damage to livestock by well-armed alien plants has been recorded in East Africa for Opuntia stricta (Australian Pest Pear) (Shackleton et al 2017) and Prosopis spp. (Bekele et al 2018), most commonly by thorns damaging hooves.…”
Section: Physical and Economic Impactsmentioning
confidence: 99%
“…Prosopis is one of the few invasive alien taxa whose ecological and economic impacts have been reasonably well studied in South Africa (van den Berg 2010; Milton and Dean 2010;Ndhlovu et al 2011Ndhlovu et al , 2016Shackleton et al 2015;Zimmermann and Pasiecznik 2005;Dzikiti et al 2018; see also Bekele et al (2018) for information from Ethiopia). The genus Prosopis includes several tree species and their hybrids that have successfully invaded the Nama-Karoo, Succulent Karoo, and semi-arid Savanna Biomes.…”
Section: Prosopis Species (Mesquite)mentioning
confidence: 99%